Argentinean Myotis (Chiroptera, Vespertilionidae), including the description of a new species from the Yungas - Novaes, Roberto Leonan M. (2022)
Myotis is the most speciose genus of mammals in the world and recent taxonomic revisions have revealed an impressive diversity of species in South America. Even so, the phenotypic conservatism of some taxa makes taxonomic delimitation difficult. We perform a taxonomic review of Myotis from Argentina based on qualitative and quantitative morphological characters. Our results confirm the occurrence of 12 species (M. albescens, M. chiloensis, M. dinellii, M. izecksohni, M. keaysi, M. lavali, M. levis, M. nigricans, M. oxyotus, M. riparius, M. ruber, and M. cf. simus) and revealed an additional new species for the Yungas Forest. The new species is small to medium (forearm length ~ 35 mm) and can be distinguished from its congeners by a set of characters that includes forearm length, cranial measurements, discrete craniodental characters, and fur color. This review does not exhaust the need for new systematic studies with Argentinean Myotis, considering the possibility of occurrence of new species and the great morphological variation found for some complex taxa.